FATAL DYSPNEOA - CASE REPORT OF A FEMALE PATIENT WITH INOPERABLE THYROID CARCINOMA - Jovanović, Anđelina; Vučić, Sanja; Valjarević, Svetlana; Vidaković, Milan; Gavrić, Jelena (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Introduction Thyroid tumors, due to their location in the neck, can threaten the respiratory tract while growing. Thyroid malignancies, in addition to compression, can also cause infiltration of local tissues. Case report Here we will present a case from the practice of a patient with advanced thyroid cancer who required urgent airway management, but due to the spread of malignancy into the mediastinum and the resulting compression on the distal parts of the trachea and lung tissue, the hospital episode ended with a fatal outcome with all medical assistance provided. Conclusion Securing the airway by endotracheal intubation or tracheotomy in a certain number of cases is not enough to save the lives of our patients. Key words: advanced thyroid cancer, dyspnea, the airway management